Radiological diagnostics in patients with pheochromocytoma - do we need to prepare? Review of the literature - Izabela Dąbrowska; Joanna Szydełko; Andrzej Wolski (Kazimierz Wielki University, 2020)
Introduction: Pheochromocytomas are chromaffin cell tumours derived from the neural crest and they are associated with catecholamine production. Radiological procedures are playing essential role in present diagnostic of adrenal glands. Physicians who send their patients to the radiological examinations should prepare them to have a safe further diagnostic. Aa well radiologist should be aware of scanning protocols to provide best quality and the safest for the patient radiological examination. Aim of the study: This article summarizes the current knowledge about radiological imaging of pheochromocytomas and scan procedures. In this paper we also want to answer to the question does a patient with pheochromocytoma need to be specially prepared for radiological procedures. Description of knowledge: Diagnostic procedures play primary role in present diagnostic and treatment of pheochomocytomas. It is crucial for further diagnostic procedures to locate the tumour and its margins.Ultrasound imaging can be used with success only in big tumours with clinical symptoms. First choice for adrenal gland tumours is always CT. That modality easily shows localisation and tumours smaller than 1 cm. Another method of choice for adrenal imaging is MRI which gives high contrast images between soft tissues. Radiological differentiation of lessions wouldn't be possible without contrast agents. They are crucial for calculations of washout in CT. Conclusions: Intravenous administration of non-ionic contrast agent for CT and gadolinium based in MRI is a safe practice for patients with pheos even without α-blocking medication. Only in an intra-arterial iodine-based contrast administration patient should be pharmacologically prepared before examination.